A comparative structural analysis of TQM,ISO/TS16949 nad organizational performance between Malaysian and Thailand automotive industry : Findings and implications - Norhayati Zakuan, author; Sha'ri Mohd. Yusof, author; Awaluddin Mohammed Shaharoun, author (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL